2015
DOI: 10.1007/s00426-015-0677-6
|View full text |Cite
|
Sign up to set email alerts
|

Professional mathematicians differ from controls in their spatial-numerical associations

Abstract: While mathematically impaired individuals have been shown to have deficits in all kinds of basic numerical representations, among them spatial-numerical associations, little is known about individuals with exceptionally high math expertise. They might have a more abstract magnitude representation or more flexible spatial associations, so that no automatic left/small and right/large spatial-numerical association is elicited. To pursue this question, we examined the Spatial Numerical Association of Response Code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 67 publications
10
89
0
4
Order By: Relevance
“…In this context, the reliabilities of comparison SNARC effects (Cipora et al, 2016;Viarouge, Hubbard, & McCandliss, 2014) In this study, we observed that the ordinal and cardinal SNARC indices were weakly correlated, but the obtained correlation vanished for standardized SNARC estimates and also especially if we extracted slope coefficients according to the best fit, categorical for ordinality and linear for numerosity. Thus, the data from this study suggest poor (if any) convergent validity for a single common construct beyond the spatial alignment of numbers and weekdays, exemplifying two cardinal and ordinal item ranges.…”
Section: Discussionmentioning
confidence: 60%
“…In this context, the reliabilities of comparison SNARC effects (Cipora et al, 2016;Viarouge, Hubbard, & McCandliss, 2014) In this study, we observed that the ordinal and cardinal SNARC indices were weakly correlated, but the obtained correlation vanished for standardized SNARC estimates and also especially if we extracted slope coefficients according to the best fit, categorical for ordinality and linear for numerosity. Thus, the data from this study suggest poor (if any) convergent validity for a single common construct beyond the spatial alignment of numbers and weekdays, exemplifying two cardinal and ordinal item ranges.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, participants with math difficulties revealed stronger SNAs than math controls (i.e., people not studying mathrelated topics; Hoffmann, Mussolin, et al, 2014), while the weakest parity SNAs were evidenced in math professionals (Cipora et al, 2016). In addition to this, number-space associations in the parity judgment task were shown to relate to spatial visualization ability, such that individuals with weaker mental rotation skills displayed stronger parity SNAs (Viarouge et al, 2014).…”
Section: Individual Differences In Number-space Associationsmentioning
confidence: 89%
“…One possible explanation for this is that number-space associations in the magnitude classification task do not depend (or to a lesser extent) on executive control, which might mediate the relationship between the parity SNAs and arithmetic performance (see Cipora et al, 2016 for the effects of mediating variables). Less involvement of executive control during magnitude classifications might well be the case, if one assumes that activation rather than inhibition of the magnitude-associated spatial code is helpful for successful task Georges,Hoffmann,& Schiltz 201 completion.…”
Section: Individual Differences In Number-space Association 200mentioning
confidence: 99%
See 2 more Smart Citations